DNA methylation is associated with inhaled corticosteroid response in persistent childhood asthmatics. Issue 9 (15th August 2019) - Wang, Alberta L.; Gruzieva, Olena; Qiu, Weiliang; Kebede Merid, Simon; Celedón, Juan C.; Raby, Benjamin A.; Söderhäll, Cilla; DeMeo, Dawn L.; Weiss, Scott T.; Melén, Erik; Tantisira, Kelan G.
Abstract: Background: Response to inhaled corticosteroids is highly variable, and the association between DNA methylation and treatment response is not known. Objective: To examine the association between peripheral blood DNA methylation and inhaled corticosteroid response in children with persistent asthma. Methods: Epigenome‐wide DNA methylation was analysed in individuals on inhaled corticosteroids in three independent and ethnically diverse cohorts—Childhood Asthma Management Program (CAMP); Children, Allergy, Milieu, Stockholm, Epidemiology (BAMSE); and Genetic Epidemiology of Asthma in Costa Rica Study (GACRS). Treatment response was evaluated using two definitions, the absence of emergency department visits and/or hospitalizations and the absence oral corticosteroid use while on inhaled corticosteroid therapy. CpG sites meeting nominal significance ( P  < 0.05) for each outcome were combined in a three‐cohort meta‐analysis with adjustment for multiple testing. DNA methylation was correlated with gene expression using Pearson and partial correlations. Results: In 154 subjects from CAMP, 72 from BAMSE, and 168 from GACRS, relative hypomethylation of cg00066816 (171 bases upstream of IL12B ) was associated with the absence of emergency department visits and/or hospitalizations ( Q  = 0.03) in all cohorts and lower IL12B expression ( ρ  = 0.34, P  = 0.01) in BAMSE. Relative hypermethylation of cg04256470 (688 bases upstream of CORT ) was associated with the absence of oral corticosteroid use ( Q  = 0.04) in all cohorts and higher CORT expression ( ρ  = 0.20, P  = 0.045) in CAMP. Conclusion and Clinical Relevance: Differential DNA methylation of IL12B and CORT are associated with inhaled corticosteroid treatment response in persistent childhood asthmatics. Pharmaco‐methylation can identify novel markers of treatment sensitivity in asthma.